Seismic vulnerability enhancement of medieval and masonry bell towers externally prestressed with unbonded smart tendons. (1st September 2016) - Preciado, Adolfo; Sperbeck, Silvio T.; Ramírez-Gaytán, Alejandro
Highlights: Seismic failure-behavior of old medieval and bell towers is accurately simulated. Numerical failure modes by FEM are in good agreement with real earthquake observations. The seismic energy dissipation is obtained by external prestressing. Proposal of two prestressing levels and one unbonded smart materials device. Medium prestressing is the optimum for towers failing ductile and quasi-brittle. Abstract: Medieval and masonry bell towers are highly vulnerable to suffer strong earthquake damage due to the mechanical and physical characteristics of masonry and other important factors. An approach for the seismic vulnerability reduction of masonry towers with external prestressing is proposed. The devices are vertically and externally located in order to be removable when needed. The characteristic flexural failure mode of medieval towers and the shear mechanism of bell towers are simulated. Both failure modes are in agreement with earthquake damage in similar towers. Medium prestressing level enhances force capacity of towers failing by bending without reducing ductility. High prestressing level slightly reduces the displacement capability of towers failing ductile. In case of belfry failure, both prestressing levels permit to increase displacement but lower force than towers failing by bending. The proposed medium prestressing level is the optimal for masonry towers and other slender structures failing by bending and shear.